Work Experience in Moderating the Independence, Competence, and Motivation of Internal Auditors on the Effectiveness of Internal Control - Lasando Lumban Gaol (JFBA: Journal of Financial and Behavioural Accounting, 2022)
Economic developments in Indonesia will have an impact on the growth of companies. Therefore, we need a system that can secure the company's assets and encourage business efficiency. Management is obliged to be able to manage the company's activities properly as the implementation of the internal auditor's accountability to the public. This study aims to examine the effect of the role of independence, competence, and motivation on the effectiveness of the internal control system of consumer goods companies in North Sumatra. Testing research data using multiple linear regression analysis and residual tests for moderating variables. The results of this study indicate that the independence, competence, and motivation of internal auditors simultaneously affect the effectiveness of the internal control system. Partially, the independence and competence of internal auditors affect the effectiveness of internal control. This is in line with the research hypothesis, but the motivation of internal auditors does not partially affect the effectiveness of internal controls. Meanwhile, work experience is not proven to moderate (strengthen or weaken) the relationship between the independence, competence, and motivation of internal auditors and the effectiveness of internal controls.